2001
DOI: 10.1007/s11864-001-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade gliomas

Abstract: Low-grade gliomas are uncommon primary brain tumors classified as histologic grades I or II in the World Health Organization (WHO) classification. The most common variants are pilocytic and low-grade astrocytomas, oligodendrogliomas, and mixed oligo-astrocytomas located in the cerebral hemispheres. Prognostic factors that predict progression-free and overall survival include young age, pilocytic histology, good Karnofsky performance status, gross total resection, lack of enhancement on imaging, and small preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 39 publications
(31 reference statements)
3
28
0
1
Order By: Relevance
“…18,19 Low-grade gliomas (WHO grades I and II) are amendable to (radio)surgical resection with curative intent, and adjuvant radiochemotherapy is only recommended for patients with incompletely resected grade II tumors or for patients older than age of 40 years regardless of the extent of resection. 20,21 In an effort to preoperatively differentiate between high-grade and low-grade lesions and to determine the optimal patient treatment, very often a stereotactic biopsy is performed preoperatively. 21 Burger et al 22 found that, among histopathologic features such as cell frequency, nuclear atypia and mitotic activity, necrosis, and vascular proliferation, only vascular proliferation differentially predicted both the short-and longterm survival in patients with anaplastic astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Low-grade gliomas (WHO grades I and II) are amendable to (radio)surgical resection with curative intent, and adjuvant radiochemotherapy is only recommended for patients with incompletely resected grade II tumors or for patients older than age of 40 years regardless of the extent of resection. 20,21 In an effort to preoperatively differentiate between high-grade and low-grade lesions and to determine the optimal patient treatment, very often a stereotactic biopsy is performed preoperatively. 21 Burger et al 22 found that, among histopathologic features such as cell frequency, nuclear atypia and mitotic activity, necrosis, and vascular proliferation, only vascular proliferation differentially predicted both the short-and longterm survival in patients with anaplastic astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In an effort to preoperatively differentiate between high-grade and low-grade lesions and to determine the optimal patient treatment, very often a stereotactic biopsy is performed preoperatively. 21 Burger et al 22 found that, among histopathologic features such as cell frequency, nuclear atypia and mitotic activity, necrosis, and vascular proliferation, only vascular proliferation differentially predicted both the short-and longterm survival in patients with anaplastic astrocytomas. To date, the detection of vascular proliferations within a malignant brain lesion places a malignant brain tumor in the WHO IV classification, and, typically, pathologic microvascularity is not uniform throughout a lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade gliomas (World Health Organisation (WHO) grade II astrocytoma, oligodendroglioma and mixed oligoastrocytoma) tend to be slow-growing tumours (Behin et al, 2003) and there remains considerable debate about the appropriate first-line treatment (Stieber, 2001;Rees, 2002). A policy of surveillance is widely accepted and active treatment in the form of surgery or radiotherapy is generally offered at the time of tumour progression.…”
mentioning
confidence: 99%
“…Currently, initial treatment consists of pharmacologic seizure control if patients present with seizures and steroids for vasogenic edema (Prabhu et al, 2010, Stieber, 2001). For patients with lesions amenable to surgery, the goal is gross total resection as many studies have found overall survival to correlate with extent of initial resection irrespective of adjuvant therapy.…”
Section: Effect Of Resection and Adjuvant Therapy On Malignant Transfmentioning
confidence: 99%